Loss of MIR15A and MIR16‐1 at 13q14 is associated with increased TP53 mRNA, de‐repression of BCL2 and adverse outcome in chronic lymphocytic leukaemia. (18th July 2014) - Lin, Ke; Farahani, Mosavar; Yang, Yi; Johnson, Gillian G.; Oates, Melanie; Atherton, Mark; Douglas, Angela; Kalakonda, Nagesh; Pettitt, Andrew R.
Summary This study was conducted to investigate the possibility that TP53 mRNA is variably expressed in chronic lymphocytic leukaemia (CLL) and that under‐expression is associated with TP53 dysfunction and adverse outcome. Although TP53 mRNA levels did indeed vary among the 104 CLL samples examined, this variability resulted primarily from over‐expression of TP53 mRNA in 18 samples, all of which lacked TP53 deletion/mutation. These patients had higher lymphocyte counts and shorter overall and treatment‐free survival times compared to cases with low TP53 mRNA expression and no TP53 deletion/mutation. Furthermore, TP53 mRNA levels did not correlate with levels of TP53 protein or its transcriptional target CDKN1A. We speculated that the adverse outcome associated with TP53 mRNA over‐expression might reflect variation in levels of MIR15A and MIR16‐1, which are encoded on chromosome 13q14 and target TP53 and some oncogenes including BCL2. In keeping with our hypothesis, 13q14 copy number and levels of MIR15A/MIR16‐1 correlated positively with one another but negatively with levels of TP53 mRNA and BCL2 mRNA. Our findings support a model in which loss of MIR15A/MIR16‐1 at chromosome 13q14 results in adverse outcome due to de‐repression of oncogenes such as BCL2, and up‐regulation of TP53 mRNA as a bystander effect.